The Role of the Maternal and Child Health Handbook in Developmental Surveillance: The Exploration of Milestone Attainment Trajectories - Hirota, Tomoya; Nishimura, Tomoko; Mikami, Misaki; Saito, Manabu; Nakamura, Kazuhiko (Frontiers in Psychiatry, 2022)
Despite the pivotal role of developmental surveillance in pediatric practice for the early detection of neurodevelopmental disorders (NDDs), there are several barriers, including scarcity of time and staff availability, to its implementation. Additionally, inadequate parental knowledge on what to expect about their child’s development contributes to potential delays in the early identification of NDDs. Home-based records (HBRs) are widely used in both high-income and low- and middle-income countries, allowing caregivers to prospectively chart the child’s development, including milestone attainment, and thus can be a useful tool for developmental surveillance. Therefore, we analyzed data on milestone attainment from birth to five years of age obtained through the home-based records (the Maternal Child Health Handbook: MCHH) in 720 children who attended the Hirosaki Five-year-old children Developmental Health Check-up Study in Hirosaki, Japan to identify trajectory patterns of milestone attainment. Parallel process latent class growth analysis on four milestone domains (motor, social interaction, communication, and self-care) revealed three different trajectories (Class 1: “Consistent milestone attainment” group; 42%, Class 2: “subtle initial delay and catch-up” group; 45%, Class 3: “Consistent failure to attain expected milestones” group; 13%). In Class 3, 90% of children were diagnosed with at least one NDDs at age 5 and approximately 65% of children had autism spectrum disorder and/or intellectual disability, the rate of which was higher than that in the other two classes. Boys and preterm-born children were more likely to be assigned to classes with less favorable trajectories of milestone attainment. Although the use of the MCHH alone does not substitute diagnostic evaluation for NDDs, our study findings suggest the potential utility of the MCHH as a tool to educate parents on what longitudinal patterns of milestone attainment are concerning and require prompt visits to professionals.